Optimizing cyanobacterial hydrogen production: metabolic and genetic strategies with glycerol supplementation - Ayshat M. Bozieva; Makhmadyusuf K. Khasimov; Mahipal S. Rao; Maria A. Sinetova; Roman A. Voloshin; Dmitry O. Dunikov; Dmitry O. Dunikov; Anatoly A. Tsygankov; Yoong Kit Leong; Yoong Kit Leong; Jo-Shu Chang; Jo-Shu Chang; et al. (Frontiers in Energy Research)
IntroductionDeveloping sustainable hydrogen production is critical for advancing renewable energy and reducing reliance on fossil fuels. Cyanobacteria, which harness solar energy through photosynthesis, provide a promising biological platform for hydrogen generation. However, improving hydrogen yields requires strategic metabolic and genetic modifications to optimize energy flow and overcome photosynthetic limitations.MethodsFour cyanobacterial species were evaluated for their hydrogen production capacities under varying experimental conditions. Photosynthesis was partially inhibited using distinct chemical inhibitors, including 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU). Exogenous glycerol was introduced as a supplementary carbon source. Hydrogen production was monitored over time, and rates were normalized to chlorophyll a content. Genomic analysis of transporter proteins was conducted to identify potential genetic loci for further enhancement of hydrogen output.ResultsNitrogen-fixing Dolichospermum sp. exhibited significantly higher hydrogen production compared to the other tested species. Supplementation with glycerol notably increased both the rate and duration of hydrogen evolution, far exceeding previously established benchmarks. The maximum hydrogen production rate for Dolichospermum sp. reached 132.3 μmol H₂/mg Chl a/h—representing a 30-fold enhancement over the rates observed with DCMU. Genomic screening revealed key transporter proteins with putative roles in carbon uptake and hydrogen metabolism.DiscussionThese findings underscore the potential of cyanobacteria, particularly Dolichospermum sp., as robust platforms for sustainable hydrogen production. The substantial improvements in hydrogen yield highlight the importance of targeted metabolic engineering and carbon supplementation strategies. Future work focused on optimizing identified transporter proteins and refining genetic interventions could further enhance biohydrogen efficiency. By leveraging the inherent photosynthetic machinery of cyanobacteria, this platform offers a renewable hydrogen source with significant promise for global energy sustainability.